Treffinger Learning Model Assisted by PPT Media is it Affects Student Learning Outcomes? - Muhammad Fath Azzajjad; H Halima; Ayu Rahayu; Dewi Satria Ahmar (CV. Media Digital Publikasi Indonesia, 2023)
The purpose of this study was to determine the effect of treffinger learning model assisted by PPT media on the learning outcomes of students in class XI MIPA SMA Negeri 1 Wundulako. This type of research is quantitative research using quasi experimental method with post-test design only design. The sample of this study amounted to 26 students of class XI MIPA 2 as an experimental class taught using the treffinger learning model assisted by PPT media and 26 students of class XI MIPA 1 as a control class taught using conventional models. Article 24 of Permendikbud No 17/2017 stipulates that the number of students in one study group is at least 20 and at most 28. Based on the results showed that the experimental class obtained an average post-test value of 72.40 while the control class obtained an average post-test value of 62.20. The normality test results obtained the significance value of the experimental class post-test 0.141 and the control class post-test 0.200 showed results > 0.05. The homogeneity test of the experimental group and the control group from the post-test results, the significance value > 0.05. Furthermore, the hypothesis test obtained a significance value of 0.002 <0.05, then H0 was rejected and H1 was accepted. So it can be concluded that there is an effect of Treffinger learning model assisted by PPT media on the learning outcomes of students in class XI MIPA SMA Negeri 1 Wundulako